Konsep Tazkiyah Al-Nafs dalam Al-Qur’an dan Implikasinya Terhadap Pendidikan Agama Islam - Aprilia, Nindy Putri; Surahman, Cucu; Sumarna, Elan (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2024)
This research aims to explore the concept of tazkiyah in the Al-Qur'an and its implications for education, especially Islamic Religious Education. This research uses library research and literature review methods, which aim to collect information and data from various sources such as books, articles and relevant journals. Data analysis was carried out using thematic analysis techniques to identify patterns and themes that emerged from the literature studied. The results of the research reveal in the Al-Qur'an Surah As-Syams verses 9-10, "It is truly fortunate for those who purify their souls, and truly it is a loss for those who pollute them." This also reveals the substantial implications of the concept of tazkiyah al-nafs in the context of Islamic Religious Education. Imam Zarnuji, in his book, emphasizes that achieving useful knowledge requires good morals, which can be obtained through the tazkiyah al-nafs process. These findings emphasize the importance of self-purification as a process in creating a clean heart, which essentially enables optimal acceptance of knowledge in the learning process. This research makes an important contribution in understanding the relationship between the purification of the soul and the effectiveness of Islamic religious education, as well as highlighting the importance of spiritual aspects in the learning process.